Raising Our Children with Disabilities in Akomimoksin - Pearl Yellow Old Woman-Healy; Stacey Running Rabbit (Disability Studies Quarterly, 2022)
Across Turtle Island there are many Indigenous families who are raising children with a disability. Personal stories can create culturally safe platforms for Indigenous parents raising what Blackfoot Elders have referred to as Sakakiitsimaitapiiksi (our treasured children), to add voice to their experiences. The purpose of this article is to share the personal stories of two mothers parenting their children with the Blackfoot teaching of Akomimoksin (love). Mothers are givers of life and often assume the primary role of caregiving, educating, navigating and advocating for their children's holistic needs. When a mother wraps her arms around a child she creates a circle and located within the sanctity of this shape is the individual she would do anything to protect. It is within these responsibilities that the intersectionalities of Indigeneity and disability are discussed and choices are made. The stories of two mothers formulating decisions designed to reclaim and reculture for the sake of their disabled Indigenous child is shared. These stories will also address similar themes that have predicated systemic encounters, transformed perspectives, resonated hope, and developed awareness that may guide others on a parallel path. It is through Akomimoskin that disability has been able to become ability.
Keywords: Blackfoot; Indigenous; families; motherhood; traditional teachings